Analysis of Energy Management and Financial Planning in the Implementation of PV Systems - Ospino Castro, Adalberto; Robles-AlgarÃn, Carlos; PeÃ±a Gallardo, Rafael (International Journal of Energy Economics and Policy, 2019)
This paper presents the analysis of energy management and financial planning that is carried out in the design and implementation of photovoltaic systems in urban areas of the city of Barranquilla, Colombia. A questionnaire with a Likert scale and 36 items was designed, which was answered by subjects with managerial functions of the 16 companies dedicated to the implementation of photovoltaic (PV) projects in Barranquilla. The instrument was validated by expert judgment with a reliability of 0.84 with Cronbach's Alpha. For the analysis of results, techniques of central tendency and variability were used. The results show that energy management in the implementation of PV projects is moderate, indicating that there is no predominant presence of indicators of improvement and energy performance in these projects. Financial planning has a moderate significance, indicating that the financial analysis methods that are being used in these PV systems projects have a basic analysis. Keywords: Energy Management, Financial Planning, Photovoltaic Energy JEL Classifications: P18, P11, Q20 DOI: https://doi.org/10.32479/ijeep.7587